Antioxidant activity and interactions between whey protein and polysaccharides from different parts of Houttuynia cordata - Liu, Xiaocui; Tian, Jin; Zhou, Zhiran; Pan, Yinzhen; Li, Zhongqiao (Frontiers in Nutrition, 2023)
Houttuynia cordata polysaccharides are known to exhibit a variety of beneficial activities, but these are currently not specifically utilized in food. Hence, using the two edible parts of Houttuynia cordata, a herbaceous plant native to Southeast Asia, this study developed polysaccharides of a stem (HCPS)-whey protein concentrate (WPC) complex and a leaf (HCPL)-WPC complex, and studied their stability, structure and antioxidant activity. The results showed that stability differed in complexes with different proportions, exhibiting only relative stability in the two complexes in which the ratio of HCPS or HCPL to WPC was 1:4, but increased stability in the HCPL-WPC complex. Structural characterization showed that there was electrostatic interaction between HCPS and WPC and between HCPL and WPC. The HCPL-WPC was found to have better antioxidant activity. The findings of this study, thus, provide a reference for the development of Houttuynia cordata polysaccharide applications in food.